A Laravel-Based Web Application for Task Monitoring and Project Management at PT X - Misbahul Munir (Yayasan Kita Menulis, 2026)
Effective project task management plays a crucial role in ensuring the operational performance of information technology companies. PT X, an Indonesian developer of Hospital Management Information Systems (SIMRS), encountered several limitations in its legacy task monitoring system developed using native PHP. These limitations included inadequate authentication mechanisms, the absence of Role-Based Access Control (RBAC), and insufficient analytical visualization to support managerial decision-making. This study aims to develop and implement a web-based task monitoring and project management system utilizing a Single Page Application (SPA) architecture based on Laravel 12, Vue.js 3, and Inertia.js. The system was developed following the Waterfall software development model, consisting of requirements analysis, system design, implementation, testing, and maintenance phases. The proposed solution comprises two integrated platforms: an Admin Panel for Product Owner teams and a Client Portal for healthcare institution clients. The system incorporates essential features such as an analytics dashboard, Kanban board, RBAC, activity logging, notification services, and Service Level Agreement (SLA) monitoring. Functional validation was conducted using the Black Box Testing method, achieving a 100% success rate across all test scenarios. The implementation of the proposed system successfully reduced manual administrative processes, enhanced project monitoring capabilities, and improved the overall efficiency of task management within the organization.